THE PROBLEM OF EVALUATING THE EFFECTIVENESS OF INFORMATION TECHNOLOGY - D. V. Akushko (Литьë и металлургия)
We consider the problems of evaluating the effectiveness of information technology (IT), particularly ERP-systems. The characteristics of the process of evaluating the effectiveness of IT for various industries are allocated and describe. The work is interdisciplinary, written at the junction of Economics and Informatics.